Public health genomics: origins and basic concepts (Italian Journal of Public Health, 2006)
Knowledge and technologies arising from the Human Genome Project promise in time to offer newopportunities for the treatment and prevention of disease. The enterprise of public health genomics aims tobridge the gap between advances in basic research and their responsible and effective implementation inclinical services and public health programmes. Public health genomics stresses the importance ofunderstanding how genes and environment act together to influence health; avoiding geneticexceptionalism; appreciating the social and political context of genomic advances; and encouraging criticalevaluation of proposed new tests and interventions. New international networks and collaborations arebeing established to develop public health genomics and further its aims.
Keywords: public health; genetics; genomics; prevention; genetic information; genetic tests